On Time Performance (OTP) Krl Ekspres Jabodetabek - Kuswati, Atik S (Warta Penelitian Perhubungan, 2010)
On time perfomance refers to the level of service remaining on the published schedule by provider. On time performance is one of many factors to indicate KRL Jabodetabek service measurement.Therefore, the passengers of KRL Jabodetabek are not convenient because of delay.This paper calculated an time performance in KRL Jabodetabek far each rute of KRL Ekspress. The method of analysis and eval.uation used score of delay such as score 1; 0,75; 0,5; 0,25 and 0,1 for range delatj 0-9 minute, 10-19 minute, 20-29 minute, 30-39 minute and 39 minute, respectively.Therefore, on time performance far departure and arrival group are categorized very poor (0-20%),poor (21%-40%), enough (41%-60%), good (61%-80%) and ven; good (81%-100%)On time performance departure is better than on time performance arrival for whole result ofon time performance analysis and evaluation in KRL Jabodetabek Express. The result of ontime performance of Bekasi expres-shows the lower which is about 73,45% and Serpongexpres represents the higger on time performance which is around 92,92%. Delay' s KRL isinfluenced by many factors such as queuing in entrance station in Gambir, Manggarai andJatinegara station Queuing in those stations is the high factor of train delay in five mounthsperiod such as 39% (Manggarai Station), 30% (Gambir Station) and 12% (Jatinegara Station).Another factor is internal factor of the train (9% ). Key words : KRL Jabodetabek Expres, KRL service, on time performance.